2022
DOI: 10.1039/d2na00495j
|View full text |Cite
|
Sign up to set email alerts
|

Exciton tuning in monolayer WSe2viasubstrate induced electron doping

Yang Pan,
Mahfujur Rahaman,
Lu He
et al.

Abstract: We report on large exciton tuning in WSe2 monolayers via substrate induced non-degenerate doping. We observe a redshift of ∼62 meV for the A exciton together with a 1-2 orders...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Interestingly, the PL spectra of 1-L WSe 2 on Si–Au NPs show red-shifted X 0 and X T peaks, compared to the peaks observed on the 1-L WSe 2 on Si NPs. This redshift is attributed to the p -type doping of 1-L WSe 2 due to electron transfer to Au . In addition, the PL intensity of the X 0 peak was higher than that of the X T peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the PL spectra of 1-L WSe 2 on Si–Au NPs show red-shifted X 0 and X T peaks, compared to the peaks observed on the 1-L WSe 2 on Si NPs. This redshift is attributed to the p -type doping of 1-L WSe 2 due to electron transfer to Au . In addition, the PL intensity of the X 0 peak was higher than that of the X T peak.…”
Section: Resultsmentioning
confidence: 99%
“…This redshift attributed to the p-type doping of 1-L WSe 2 due to electron transfer to Au. 72 In addition, the PL intensity of the X 0 peak was higher than that of the X T peak. This is caused by the transfer of electrons from 1-L WSe 2 to Au, which increases the hole concentration, resulting in a higher radiative recombination rate for X 0 and a lower intensity for X T emission.…”
Section: Optical Characterizationmentioning
confidence: 95%
“…We believe that the deep knowledge of the optical properties (i.e. dielectric function and PL) of hBN-encapsulated vdW homo-and heterostacks by means of spectroscopies with a resolution at the microand nanoscale [85,86] is pivotal for their exploitation in novel devices.…”
Section: Resultsmentioning
confidence: 99%
“…12 It has been demonstrated that morphological and structural arrangements of nanomaterials play crucial roles in their properties, and therefore the performance of devices can be regulated by precisely controlling morphology and structure. 13−19 Various techniques have been explored to manipulate the excitonic and electronic characteristics of monolayer TMDs, including strain, 20,21 layer-dependent engineering, 22 electron doping, 23,24 plasma treatment, 25 alterations in dielectric environments, 26 and the application of external electric fields. 27 Within the realm of TMDs, monolayer WSe 2 has gained prominence due to its potential as a single-photon source 28,29 and its relevance to quantum information processing, 30−32 attributed to its optical dark exciton ground state.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Notably, monolayer TMDs can exhibit direct band gap properties and emit bright photoluminescence (PL), positioning them as clear candidates for next-generation optoelectronic devices . It has been demonstrated that morphological and structural arrangements of nanomaterials play crucial roles in their properties, and therefore the performance of devices can be regulated by precisely controlling morphology and structure. Various techniques have been explored to manipulate the excitonic and electronic characteristics of monolayer TMDs, including strain, , layer-dependent engineering, electron doping, , plasma treatment, alterations in dielectric environments, and the application of external electric fields …”
Section: Introductionmentioning
confidence: 99%